AN ANALYSIS OF STUDENTS MOTIVATION IN EXTENSIVE LISTENING FOR THE SECOND SEMESTER AT UNIVERSITAS PGRI SILAMPARI - Syaprizal; Ayu Oktaviani; Liyana, Irma (Universitas Negeri Surabaya, 2024)
The researcher formulated the problem What are the students’ motivation in Extensive Listening for the second semester at Universitas PGRI Silampari. In addition, the objectives of this research was to find out to describe the students motivation in Extensive Listening. This research will be conducted by using qualitative as well as descriptive method and it is designed to find out some information from actual condition. The subject of the research is the students of second semester at Universitas PGRI Silampari and the researcher collected the data based on the questionnaire is made based on google form for main data for supporting the data as the research instrument. The data from the online questionnaire was put into a table and summarized in form of percentages for each part of the questionnaire. The result of distributing students questionnaire consist of indicator included 20 statements for the second semester with a total of 24 students’ was explained descriptively by using the percentages.